AKIBAT KEBERGANTUNGAN ALIH TEKNOLOGI BAGI NEGARA SEDANG BERKEMBANG - Bakti Trisnawati (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
Technology transfer in terms of business is an asset created through investment with high risk and large costs. On the other hand, mastering technology enables the owner to gain strength not only in the economic field, but also socially, as well as politically. Therefore, it is natural for technology owners to try to maintain the technology they have. However, due to dependence on technology, developing countries have to pay high prices for the purchase of these technologies. In addition, developing countries are also not able to exercise control of the industries built, and also will not succeed in develop“indigenous technological capability”.